Oral health promotion and prevention of Early Childhood Caries - Ungchusak, Chantana (Thai Dental Public Health Journal, 2017)
Dental caries is a common childhood chronic disease which affects not only oral health of children but also their quality of life and their families. This paper reviewed the effectiveness of various preventive measures, categorized as primary, secondary and tertiary prevention. Primary prevention includes oral health education, tooth-brushing with fluoridated toothpaste, water fluoridation, fluoridated milk, and dietary control. Systematic reviews showed that effectiveness of simple health education for the prevention of ECC is limited. However, health education in conjunction with motivational intervention, active hands-on training, regular home visit, or with professional preventive programmes showed some promise results. Educational programmes that integrated with other health issues were also found more effective than simple oral health education alone. For fluoride strategies, water fluoridation is accepted as a high cost-effectiveness measure and most equitable method in dental health across social classes. Fluoridated milk, when provide before the age of 4 years, showed caries preventive effect on primary teeth. There is also evidence from systematic reviews and meta-analysis that tooth brushing with fluoridated toothpaste at least 1,000 ppm fluoride concentration, as home care intervention or school programs, is a cost effective way in reducing dental caries for young children. Sugar is a common risk to a number of other non-communicable diseases. The ‘common risk approach’, by multidisciplinary collaboration, as well as food policy development to reduce sugar consumption, is necessary. Fluoride varnish, as secondary prevention, can decrease caries incidence in early childhood. 10% providone iodine has been shown to provide some benefit to control of microbial colonization after treatment for severe ECC but for a limited period of time. Filling decayed teeth can be considered as tertiary prevention. The benefits of restoration not only help delay the new colonization of microorganism, but also enhance the healthy ecology of mouth and good nutrition of children.